Vector Measures, Integration and Related Topics - Curbera, Guillermo P.; Mockenhaupt, Gerd.; Ricker, Werner J.; SpringerLink (Online service) (Basel : Birkhäuser Basel, 2010)
This volume contains a selection of articles on the theme "vector measures, integration and applications" together with some related topics. The articles consist of both survey style and original research papers, are written by experts in the area and present a succinct account of recent and up-to-date knowledge. The topic is interdisciplinary by nature and involves areas such as measure and integration (scalar, vector and operator-valued), classical and harmonic analysis, operator theory, non-commutative integration, and functional analysis. The material is of interest to experts, young researchers and postgraduate students.
On Mean Ergodic Operators -- Fourier Series in Banach spaces and Maximal Regularity -- Spectral Measures on Compacts of Characters of a Semigroup -- On Vector Measures, Uniform Integrability and Orlicz Spaces -- The Bohr Radius of a Banach Space -- Spaces of Operator-valued Functions Measurable with Respect to the Strong Operator Topology -- Defining Limits by Means of Integrals -- A First Return Examination of Vector-valued Integrals -- A Note on Bi-orthomorphisms -- Compactness of Multiplication Operators on Spaces of Integrable Functions with Respect to a Vector Measure -- Some Applications of Nonabsolute Integrals in the Theory of Differential Inclusions in Banach Spaces -- Equations Involving the Mean of Almost Periodic Measures -- How Summable are Rademacher Series? -- Rearrangement Invariant Optimal Domain for Monotone Kernel Operators -- The Fubini and Tonelli Theorems for Product Local Systems -- A Decomposition of Henstock-Kurzweil-Pettis Integrable Multifunctions -- Non-commutative Yosida-Hewitt Theorems and Singular Functionals in Symmetric Spaces of ?-measurable Operators -- Ideals of Subseries Convergence and Copies of c 0 in Banach Spaces -- On Operator-valued Measurable Functions -- Logarithms of Invertible Isometries, Spectral Decompositions and Ergodic Multipliers -- Norms Related to Binomial Series -- Vector-valued Extension of Linear Operators, and Tb Theorems -- Some Recent Applications of Bilinear Integration -- A Complete Classification of Short Symmetric-antisymmetric Multiwavelets -- On the Range of a Vector Measure -- Measure and Integration: Characterization of the New Maximal Contents and Measures -- Vector Measures of Bounded ?-variation and Stochastic Integrals -- Does a compact operator admit a maximal domain for its compact linear extension? -- A Note on R-boundedness in Bidual Spaces -- Salem Sets in the p-adics, the Fourier Restriction Phenomenon and Optimal Extension of the Hausdorff-Young Inequality -- L-embedded Banach Spaces and a Weak Version of Phillips Lemma -- When is the Space of Compact Range Measures Complemented in the Space of All Vector-valued Measures? -- When is the Optimal Domain of a Positive Linear Operator a Weighted L 1-space? -- Liapounoff Convexity-type Theorems.
Keywords: Mathematics; Operator theory; Mathematics; Measure and Integration; Operator Theory